Efficient diode pumped ytterbium-doped fibre laser - Harun, Sulaiman Wadi; Paul, M.C.; Moghaddam, M.R.A.; Das, S.; Sen, R.; Dhar, A.; Pal, M.; Bhadra, S.K.; Ahmad, Harith (Institution of Engineering and Technology, 2010)
A highly efficient laser action from a ytterbium-doped fibre (YDF) is demonstrated using a fibre Bragg grating at room temperature. The YDF used is drawn from a Yb2O3-doped preform, fabricated through deposition of a porous layer of composition SiO2-GeO2 by the MCVD process in conjunction with a solution doping technique. The fibre laser operates at a wavelength of 1028 nm with maximum slope efficiency of 88% when pumped by a singlemode 977 nm laser diode.